Chronic kidney disease and cardiovascular risk in six regions of the world (ISN-KDDC): a cross-sectional study - Dr. Bogdan Ene-Iordache, PhD; Norberto Perico, MD; Boris Bikbov, MD; Sergio Carminati, IT; Andrea Remuzzi, EngD; Annalisa Perna, MSc; Nazmul Islam, MD; Rodolfo Flores Bravo, MD; Prof. Mirna Aleckovic-Halilovic, MD; Prof. Hequn Zou, MD; Prof. Luxia Zhang, MD; Zaghloul Gouda, MD; et al. (Elsevier, 2016)
Background: Chronic kidney disease is an important cause of global mortality and morbidity. Data for epidemiological features of chronic kidney disease and its risk factors are limited for low-income and middle-income countries. The International Society of Nephrology's Kidney Disease Data Center (ISN-KDDC) aimed to assess the prevalence and awareness of chronic kidney disease and its risk factors, and to investigate the risk of cardiovascular disease, in countries of low and middle income. Methods: We did a cross-sectional study in 12 countries from six world regions: Bangladesh, Bolivia, Bosnia and Herzegovina, China, Egypt, Georgia, India, Iran, Moldova, Mongolia, Nepal, and Nigeria. We analysed data from screening programmes in these countries, matching eight general and four high-risk population cohorts collected in the ISN-KDDC database. High-risk cohorts were individuals at risk of or with a diagnosis of either chronic kidney disease, hypertension, diabetes, or cardiovascular disease. Participants completed a self-report questionnaire, had their blood pressure measured, and blood and urine samples taken. We defined chronic kidney disease according to modified KDIGO (Kidney Disease: Improving Global Outcomes) criteria; risk of cardiovascular disease development was estimated with the Framingham risk score. Findings: 75 058 individuals were included in the study. The prevalence of chronic kidney disease was 14·3% (95% CI 14·0-14·5) in general populations and 36·1% (34·7-37·6) in high-risk populations. Overall awareness of chronic kidney disease was low, with 409 (6%) of 6631 individuals in general populations and 150 (10%) of 1524 participants from high-risk populations aware they had chronic kidney disease. Moreover, in the general population, 5600 (44%) of 12 751 individuals with hypertension did not know they had the disorder, and 973 (31%) of 3130 people with diabetes were unaware they had that disease. The number of participants at high risk of cardiovascular disease, according to the Framingham risk score, was underestimated compared with KDIGO guidelines. For example, all individuals with chronic kidney disease should be considered at high risk of cardiovascular disease, but the Framingham risk score detects only 23% in the general population, and only 38% in high-risk cohorts. Interpretation: Prevalence of chronic kidney disease was high in general and high-risk populations from countries of low and middle income. Moreover, awareness of chronic kidney disease and other non-communicable diseases was low, and a substantial number of individuals who knew they were ill did not receive treatment. Prospective programmes with repeat testing are needed to confirm the diagnosis of chronic kidney disease and its risk factors. Furthermore, in general, health-care workforces in countries of low and middle income need strengthening. Funding: International Society of Nephrology.